Adult supratentorial extraventricular anaplastic ependymoma with cerebrospinal fluid dissemination metastases: a case report - Zhang, Daojin; Liu, Hongbing; Zhang, Maosong; Cao, Jun (Frontiers in Neurology, 2024)
Background Ependymomas mostly locate in the infratentorial region and often occur in children. Anaplastic ependymomas account for 45–47% of supratentorial and 15–17% of infratentorial ependymomas, also known as malignant ependymomas. Adult supratentorial extraventricular anaplastic ependymoma (SEAE) is rare in clinical practice, and only a few cases have been reported so far, and there is no clinical study with large sample size. We report a case of adult supratentorial extraventricular anaplastic ependymoma in the occipital lobe with cerebrospinal fluid dissemination metastases. Case description A 58-year-old female patient presented with unexplained pain in multiple parts of the body for the past half a year, mainly manifested as pain in the head, abdomen and chest. On August, 2022, Head MRI of the patient showed abnormal signal shadow in the left occipital lobe, which was considered a malignant lesion. The patient underwent tumor resection under general anesthesia on September 3, 2022. Postoperative pathological examination showed anaplastic ependymoma. The postoperative follow-up head MRI showed multiple cerebrospinal fluid dissemination metastases in the brain. Conclusion Adult SEAE is a rare tumor with high malignancy and have a tendency to disseminate into the CSF, resulting in drop metastases. Immunohistochemistry is very important for the diagnosis of SEAE. It is recommended to administer adjuvant chemotherapy or radiation therapy appropriately after surgery, based on the tumor being completely resected as much as possible.